Usulan Perbaikan Kualitas Kualitas terhadap Produk Cacat dengan Menggunakan Metode Fault Tree Analysis (FTA) dan Failure Mode And Effect Analysis (FMEA) di CV X - Ikania Oktavialli; Asep Nana Rukmana; Iyan Bachtiar (UNISBA Press, 2023)
Abstract. CV. X is a company engaged in the manufacturing industry that produces footwear. The production system carried out at the company uses the